Sistemas de cultivo do morangueiro no sul de Minas Gerais: riscos químicos associados à cultura e contribuições à saúde do agricultor familiar - Morales, Valdir (2018)
This work, considering the strawberry production in southern Minas Gerais, discusses the chemical risks to the health of family farmers caused by the use of pesticides, aiming at changing the prospects of a production based on intensive use of chemicals when compared to an agroecological bases prospect. The applied methodology was the snowball sampling, with the application of a structured questionnaire, raising social characteristics of the producers and techniques of production management. Assessing the chemical risks associated with strawberry production is nothing more than the motto for discussing the chemical risks associated with the practice of large-scale agricultural production, its motivators, its history, the beneficiaries, the ethical question, who benefits, and who is harmed in this eternal dialectic of winning and losing. It was verified that the region under study predominantly presents the conventional production in strawberry monocultures with risks to the health of the family farmer. Organic production is also present, with most of the productive designs being tied to the monoculture model, which is far from the agroecological bases. However, there are examples of organic production that prioritize crop diversity management , which are close to the agroecological principles. Different levels of technification were found, allowing the analysis of the profile of strawberry production in the locality, which is linked to family production and intensive use of pesticides, but with different local initiatives of non-use of these products. Thus, it is concluded that it is possible to produce healthy, safe and environmentally safe food. There is a possibility of eliminating the danger that exists in this model of industrial production, which devalues the need for knowledge of the ecosystem, ecology, and nature, denying it, and creating an artificial environment for food production, in a system of segregation and privatization of knowledge. There are great challenges, such as the need for self-organization of producers, greater performance of Federal, State and Municipal official public agencies in the locality regarding the organization of producers and the way of conducting productive management.